Transcriptomic Analysis of Thermally Stressed Symbiodinium Reveals Differential Expression of Stress and Metabolism Genes - Gierz, Sarah L.; Forêt, Sylvain; Leggat, William (Frontiers in Plant Science, 2017)
Endosymbioses between dinoflagellate algae (Symbiodinium sp.) and scleractinian coral species form the foundation of coral reef ecosystems. The coral symbiosis is highly susceptible to elevated temperatures, resulting in coral bleaching, where the algal symbiont is released from host cells. This experiment aimed to determine the transcriptional changes in cultured Symbiodinium, to better understand the response of cellular mechanisms under future temperature conditions. Cultures were exposed to elevated temperatures (average 31 °C) or control conditions (24.5 °C) for a period of twenty-eight days. Whole transcriptome sequencing of Symbiodinium cells on days four, nineteen and twenty-eight were used to identify differentially expressed genes under thermal stress. A large number of genes representing 37.01% of the transcriptome (~23,654 unique genes, FDR < 0.05) with differential expression were detected at no less than one of the time points. Consistent with previous studies of Symbiodinium gene expression, fold changes across the transcriptome were low, with 92.49% differentially expressed genes at ≤ 2-fold change. The transcriptional response included differential expression of genes encoding stress response components such as the antioxidant network and molecular chaperones, cellular components such as core photosynthesis machinery, integral light-harvesting protein complexes and enzymes such as fatty-acid desaturases. Differential expression of genes encoding glyoxylate cycle enzymes were also found, representing the first report of this in Symbiodinium. As photosynthate transfer from Symbiodinium to coral hosts provides up to 90% of a coral’s daily energy requirements, the implications of altered metabolic processes from exposure to thermal stress found in this study on coral-Symbiodinium associations are unknown and should be considered when assessing the stability of the symbiotic relationship under future climate conditions.